Assessment of grief in mothers with pregnancy loss and role of post bereavement counselling: a prospective study - Bamniya, Jaishree Surendrakumar; Bhatia, Gopal Omprakash; Doshi, Haresh Umedchand; Ladola, Harshad Manilal (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2018)
Background: Pregnancy is usually a joyful experience for a woman. It is one of the milestones that, even though sometimes stressful, is rewarding for the reason that the woman takes on a new level of responsibility. Objective of present study was to assess the psychological problems associated with Pregnancy loss and effectiveness of post bereavement counselling in subjects with perinatal grief. Methods: This was a prospective study. This study was conducted at Obstetrics and Gynecology Department of GCS Medical College and Hospital from January 2013 to June 2016 in collaboration with Psychiatrist of evaluation of subjects. A total of 404 patients were taken in the study. All patients with pregnancy loss including abortions, ectopic pregnancy, Intrauterine death, Stillbirth and neonatal deaths who consented to be a part of study were included in the study. After taking informed consent, study participants were assessed for perinatal grief by Perinatal Grief scale -33(PGS-33). Results: Results indicate that the process of active grief begins to occur soon after loss and resolves itself over time if no complicating factors are present. Time was found to interact with other factors in the grieving process. The number of perinatal losses, time, and the presence of living children were related to the difficulty with coping subscale of the PGS-S. Conclusions: Though time is the best healer, intervention in the form of counselling can be beneficial for patients with difficult coping and despair. Our experience with PGS-33 was that it is not very user friendly especially for patients with low education status. So, changes should be made to further simply such scales so it can be used widely and assessment should be simplified.